Dampak Perilaku Phubbing Terhadap Interaksi Sosial Asosiatif Mahasiswa Tadris IPS Ekonomi UIN Mataram - Budiman; Majid, M. Nurholis; Hizam, Ibnu; Bahri, Saiful; Turmuzi, Ahmad (Alpatih Harapan Semesta, 2025)
This study aims to analyze the impact of phubbing behavior on the associative social interaction of students in the Tadris Social Science-Economics program at UIN Mataram and to identify the underlying causes of such behavior. Using a qualitative approach with field research methods, data were collected through observation, interviews, and documentation. The findings indicate that phubbing behavior is triggered by social media use, online gaming, situational factors, and social influence. Characteristics of phubbing behavior include excessive smartphone use, anxiety when not using a smartphone, frequent screen-checking, and a preference for digital communication. The impact of phubbing on students’ associative social interaction includes feelings of being unappreciated, weakened friendships, reduced communication quality, and decreased cooperation. These results highlight that phubbing poses a significant challenge to fostering healthy social relationships in academic settings, emphasizing the need for digital awareness and strategies to strengthen face-to-face social interaction.